2019
DOI: 10.21203/rs.2.12016/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anatomic features of mandibular second molars root canals in a Yemeni population: cone-beam computed tomography

Abstract: Background: This study aimed to identify and characterize root and canal morphology and the prevalence of C-shaped canals of mandibular second molars (MSMs) in a Yemeni population using cone-beam computed tomography (CBCT). Methods: CBCT images of 500 right and left MSMs with mature roots were taken from 250 Yemeni individuals and analyzed for the following features: number of roots, total number of canals orifices within the tooth and number of canals orifices in each root, type of roots, either fused or sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…4.9% of 411 Malaysian subpopulation 17 & 9.3% in1702 Malaysian subpopulation 34 . However, a study on a Brazilian subpopulation showed 22% for a second canal in mandibular canine 35 and another study on Georgian populations reported 31.8 % for a second canal 36 .…”
Section: Discussionmentioning
confidence: 91%
“…4.9% of 411 Malaysian subpopulation 17 & 9.3% in1702 Malaysian subpopulation 34 . However, a study on a Brazilian subpopulation showed 22% for a second canal in mandibular canine 35 and another study on Georgian populations reported 31.8 % for a second canal 36 .…”
Section: Discussionmentioning
confidence: 91%